Penerapan Terapi Relaksasi Benson untuk Menurunkan Tekanan Darah pada Lansia dengan Hipertensi di Panti Werdha - Novri Wijaya; Lilik Pranata; Aniska Indah Fari (Jurnal Siti Rufaidah, 2026)
Hypertension is a chronic disease that has a major impact on the health of the elderly and is often a major challenge in geriatric institutions. One of the effective, safe, and holistic non-pharmacological therapies to overcome this condition is Benson Relaxation Therapy. This study aims to analyze the effectiveness of the application of Benson relaxation therapy in reducing blood pressure in elderly with hypertension at the Dharma Bhakti Werdha Home through an Evidence-Based Practice (EBP) approach. The research design used was a descriptive case study with three respondents, namely Mrs. A, Mrs. N, and Mrs. S. The intervention was carried out twice a day with a duration of 10–15 minutes for three consecutive days. The results showed a consistent decrease in blood pressure in all three respondents after the intervention. Mrs. A's blood pressure dropped from 158/78 mmHg to 148/75 mmHg, Mrs. N from 160/83 mmHg to 150/79 mmHg, and Mrs. S from 157/87 mmHg to 148/82 mmHg. Physiologically, this technique works by stimulating the parasympathetic nervous system and reducing stress hormones, resulting in vasodilation of blood vessels. Benson relaxation therapy has been shown to be an effective, safe, and inexpensive non-pharmacological intervention to help control blood pressure and improve the psychospiritual well-being of elderly people in nursing homes.